Enhancing Disaster Preparedness Capacity and Multi-Stakeholder Coordination through Penta-Helix Collaboration: The Role of Kwarda DIY in Regional Resilience - Helen Dian Fridayani; Yuli Isnadi; Muhammad Eko Atmojo; Aidilla Qurotianti; Sindy Widyasari (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: Indonesia is famous for its disaster-prone status, having been situated along the Pacific Ring of Fire which makes areas like the Special Region of Yogyakarta vulnerable to various disasters such as earthquakes, floods, and volcanic eruptions. Nevertheless, disaster preparedness is still low; community and organizational preparedness, especially related to technical capacity and cross-sector coordination, continue to be a challenge. In terms of community-based disaster preparedness, such functions from intermediary civic organizations, such as Kwartir Daerah (Kwarda) of the Indonesian Scout Movement, have not been employed effectively. Purpose of Study: It is the purpose of this study to formulate and evaluate a penta-helix collaborative disaster mitigation model for Kwarda, which would be intended to further the organization's preparedness capacity and, through cross-sector coordination, augment regional resilience. Methods: The approach of community-based research (CBR) design with Kwarda and community stakeholders placed as active co-authors of the research. It is based on the penta-helix framework, which includes five actors: government, academia, private sector, community, and media. Research stages (problem identification, participatory planning, implementation, evaluation). Program interventions include disaster preparedness education, simulation-based exercises, coordination strengthening activities, and development of contingency planning mechanisms. A pre-test and post-test design, complemented by qualitative observation, measured the test scores of 50 subjects. Results: These results include improvements in disaster preparedness capacity of the participants through improvements in knowledge score average, which increased from 58.2 (pre-test) up to 81.4 (post-test), or 39.9% increases. Moreover, qualitative findings show improved coordination capacity with faster response times, more systematic evacuation procedures, and stronger stakeholder cooperation during the simulation activities.